Supply chain management practices in pharmaceuticals industry: A study on Eskayef Pharmaceuticals Limited - Khan, Amin Hasan (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2021.